Probe – Integrated electrochemical sensing platform for detection of trace levels of Dapoxetine hydrochloride drug residue in water and drug formulations - H. Alwael; N.A. Asiri; B.G. Alhogbi; A.S. Alharthi; E.A. Bahaidarah; T.N. Abduljabbar; D.F. Baamer; M. Madkour; F.A. Zainy; M.S. El-Shahawi (Electrochemistry Communications, 2025)
The extensive use and misuse of selective serotonin reuptake inhibitors (SSRIs) in drug formulations has resulted in their accumulation in food sources and environment, posing noteworthy threats to human health and the global economy. Dapoxetine hydrochloride (DPH) is one of the recent oral drugs frequently misused for the treatment of male sexual dysfunction of premature ejaculation and has lately international attention. Hence, the current study reports a simple and low cost electrochemical probe based on glassy carbon electrode (GCE) combining adsorptive square wave - anodic stripping voltammeter (Ads SW-ASV) for detection of DPH in aqueous solution at pH 3. The proposed probe displayed limits of detection (LOD) and quantification (LOQ) of 5.0 × 10−7 and 1.56 × 10−6 M, respectively, with a wide linear dynamic range (LDR) of 1.0 × 10−6–1.0 × 10−4 M of DPH. The sensor also revealed remarkable reproducibility, stability, and resistance towards interference. The probe also has favorable LOD and good LDR compared to the recent reported assays for DPH detection. The probe was applied for detection of DPH in its drug formulations and its residues in water samples with acceptable recoveries (98.5 ± 0.014–104 ± 0.016 %) with favorable repeatability and reproducibility. The experimental Student texp test (n = 5) was lower than tabulated t value t (2.78) at 95 % confidence (n = 5) demonstrating the reliability of the probe towards DPH detection in water and signifying the potential practices for DPH detection in complex matrices. Thus, the probe revealed good performance making it a talented candidate for practical detection of DPH. Interference of some frequently found components in drug residues in water and long-term stability of the probe was also assigned. The probe is simple, robust, and able to detect DPH in complex matrix with high recoveries.